2003
DOI: 10.1128/aac.47.3.905-909.2003
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Activity of Colistin and Ceftazidime against Multiantibiotic-Resistant Pseudomonas aeruginosa in an In Vitro Pharmacodynamic Model

Abstract: Despite the marketing of a series of new antibiotics for antibiotic-resistant gram-positive bacteria, no new agents for multiple-antibiotic-resistant gram-negative infections will be available for quite some time. Clinicians will need to find more effective ways to utilize available agents. Colistin is an older but novel antibiotic that fell into disfavor with clinicians some time ago yet still retains a very favorable antibacterial spectrum, especially for Pseudomonas and Acinetobacter spp. Time-kill curves f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(94 citation statements)
references
References 15 publications
6
85
0
3
Order By: Relevance
“…Numerous studies have been performed in recent years using a pharmacodynamic model or standard time-kill studies of the effect of polymyxin B or colistin against strains of P. aeruginosa (19,59,67,93,107,166), A. baumannii (60,88,106,136,160,170), and K. pneumoniae (20). Nearly all studies demonstrated that the polymyxins produce concentration-dependent killing, with an initial kill followed by regrowth.…”
Section: Bactericidal Activity and Synergy Studiesmentioning
confidence: 99%
“…Numerous studies have been performed in recent years using a pharmacodynamic model or standard time-kill studies of the effect of polymyxin B or colistin against strains of P. aeruginosa (19,59,67,93,107,166), A. baumannii (60,88,106,136,160,170), and K. pneumoniae (20). Nearly all studies demonstrated that the polymyxins produce concentration-dependent killing, with an initial kill followed by regrowth.…”
Section: Bactericidal Activity and Synergy Studiesmentioning
confidence: 99%
“…20 There are few experimental and clinical studies in the literature regarding combinations of colistin with other antibiotics, such as beta-lactams, rifampin, amikacin, trimethoprim-sulfomethoxazole and ciprofloxacin, against multidrug-resistant Gram-negative bacteria. 13,[21][22][23][24] In a recent study, we have shown the existence of in-vitro synergy between colistin methanesulfonate and amikacin in 12% of 50 P. aeruginosa strains isolated from CF patients. 25 In the present study, synergistic interactions were seen in two of seven clinical strains.…”
Section: Discussionmentioning
confidence: 99%
“…13 Lung tissue penetration of colistin following i.v. infusion is unknown, and pharmacokinetic studies have been reported recently.…”
Section: Discussionmentioning
confidence: 99%
“…Besides colistin alone, antibiotic combinations including colistin will be a new therapeutic option for the treatment of multidrug-resistant strains, if in-vitro data correlate well with clinical studies (1,5,12). Again, determining a standardized breakpoint is important for interpretation of these synergy studies.…”
Section: Discussionmentioning
confidence: 99%